Modelling of radiocesium transfer in the lichen-reindeer/caribou-wolf food chain - Holleman, D. F.; White, R. G.; Allaye-Chan, A. C. (Rangifer, 1990)
The environmental contaminate radiocesium (cesium-137) has been shown to be of value as a marker in food selection and intake studies. Its greatest potential value as a food marker is in the subarctic/arctic regions, particularly in the lichen to reindeer/caribou to wolf food chain. A kinetic model describing the movement of radiocesium through the food chain has been developed using the SAAM computer program and is presented here. The program has been written so that the various paramenters affecting the transfer of radiocesium in the food chain can be altered more realistically to describe the system being modeled. The values of the parameters as given in this example are realistic for interior Alaska, however caution should be exercised in the application of the present results to regions that may be vastly different from the Alaskan interior without first evaluating the parameters and assumptions of the model.